Logics of Domains - Zhang, Guo Qiang (DAIMI Report Series, 1989)
This dissertation studies the logical aspects of domains as used in the denotational semantics of programming languages. Frameworks of domain logics are introduced which serve as basic tools for the systematic derivation of proof systems from the denotational semantics of programming languages. The proof systems so derived are guaranteed to agree with the denotational semantics in the sense that the denotation of any program coincides with the set of assertations true of it. The study focuses on two frameworks for denotational semantics: the sep domains, and the less standard, but important, category of dI-domains with stable functions